Implications of inequality aversion for international climate policy - Carsten Vogt; Bodo Sturm (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
In this paper, we extend the Fehr and Schmidt model of inequality aversion to a situation where the players differ with respect to their benefits and costs from contributions to a non-linear public good. A necessary condition for contributing to the public good is that the players' benefit exceeds some critical value. Using data from the impact assessment model RICE and estimates for inequality aversion from the experimental literature, we show that this condition fails to hold for major countries involved in international climate policy.
Keywords: C72; D63; H41; Q54; 330; Climate policy; public good game; inequality aversion; voluntary cooperation; Klimaschutz; Öffentliches Gut; Spieltheorie; Gerechtigkeit; Trittbrettfahrerverhalten; Welt